PEMAHAMAN MASYARAKAT TERHADAP KOMUNIKASI ILMU PENGETAHUAN DAN TEKNOLOGI - Teuku Reiza Yuanda (Jurnal Sosioteknologi, 2008)
The scientific community faces many challenges, from the funding of scientific research to the public communication of science and technology. A better understanding of science and technology's complex dynamics and interactions with the society, taking the opinions of the general public into account, has also been found useful for the endeavour to increase access to knowledge and move towards social control of science and technology's innovation. Such research will contribute to better knowledge of how knowledge operates in society, as well as serving the practical needs of those concerned with improving public understanding of science and technology.